Chokeberry (X Sorbaronia mitschurinii) for health - Marnila, P.; Shikov, A. N.; Laine, A.; Kaseva, J.; Hellström, J.; Pihlava, J.-M.; Pozharitskaya, O. N.; Kauppinen, S.; Makarov, V. G.; Makarova, M. N.; Mattila, P.; Galambosi, B. (Natural Resources Institute Finland, Luke, 2016)
High consumption of berries and fruits as whole (not as high sugar juices) have in numerous clinical studies consistently shown to have an anti-obesity effect. There are several mechanisms behind. A part of them are attributed to phytochemicals including phenolic compounds. Obesity is associated with increased risk for widespread diseases, including hypertension, metabolic syndrome, type II diabetes, atherosclerosis and arthritis, disorders with increasing incidence. Chokeberries are exceptionally rich source of phenolic compounds. The content of total phenolics is so high that no other common edible fruit or berry can surpass it. The beneficial effects of chokeberry juice on lipid metabolism are well documented. Chokeberry is considered to be beneficial food for diabetes patients. An interesting new area is the effects of berries and fruits on central nervous system. Hypertension is an important risk factor for cardiovascular disease which is the most common cause of morbidity and mortality in Europe, usually due to atherosclerosis. Chokeberry phenolic extracts have in clinical trials been shown to reduce blood pressure in hypertensive patients. In Specicrop project we studied effects of different dosages of Finnish chokeberry (X Sorbaronia mitschurinii, var. Viking) juice on blood pressure of the spontaneously hypertensive rats. We also measured the inflammatory cytokines in rat blood in order to see the potential beneficial effects of the chokeberry juice on chronic inflammation which is typical in hypertension. The study provided encouraging data.
Keywords: Aronia mitschurinii; diabetes meilitus; terve aineenvaihdunta; phenolic compounds; polyphenols; hypertension; vascular disease; inflammation; metabolic health; fenolit; verenpaine; aineenvaihdunta; fenoliset yhdisteet; polyfenolit; verenpainetauti; tulehdus